2000
DOI: 10.1046/j.1365-2672.2000.00795.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the microbial contamination of beef carcass tissue with a rapid chromogenic Limulus amoebocyte lysate endpoint assay

Abstract: A chromogenic Limulus amoebocyte lysate (LAL) endpoint assay was found to be an accurate and rapid means of gauging levels of beef carcass microbial contamination within 10 min. The assay demonstrated a high correlation with the total mesophilic bacterial and coliform surface populations from inoculated beef carcass surface tissues. This assay was tested on a set of actual beef carcass surface samples (n = 121) demonstrating the utility of the chromogenic LAL test as a means of monitoring carcass microbial con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…Endotoxin was measured using the chromogenic LAL endpoint assay, which is based on the activation of a clotting enzyme in the lysate (14). The LAL test was purchased from Charles River Endosafe (Charleston, SC, USA).…”
Section: Endotoxin Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Endotoxin was measured using the chromogenic LAL endpoint assay, which is based on the activation of a clotting enzyme in the lysate (14). The LAL test was purchased from Charles River Endosafe (Charleston, SC, USA).…”
Section: Endotoxin Analysismentioning
confidence: 99%
“…This assay was applied in several studies as a quick, alternative method for microbiological testing and hygiene control of fi sh (12,13) and meat (14). Several studies demonstrated a high correlation between the LAL test and the microbial quality of the products (12,14). Currently, this test has not been applied in testing the freshness/spoilage of non-fin fish.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous other studies have reported the application of the LAL assay in the food industry, as a better way of monitoring microbial contamination (Siragusa et al 2000) and to evaluate the influence of standard heat treatment and chemical preservation with sodium benzoate on the changes in LPS-related endotoxicity of food-borne pothogenic micro-organisms (Abraham et al 2009b). …”
Section: Resultsmentioning
confidence: 99%
“…However, the values of ATP are variable in foods and a specific instrument is needed for the ATP analysis (Siragusa et al 1995). Chromogenic Limulus amoebocyte lysate (LAL) test was reported for estimating aerobic plate counts and coliform counts; however, the test only monitors lipopolysaccharide in Gram-negative bacteria (Siragusa et al 2000).…”
Section: Discussionmentioning
confidence: 99%